A note upon localism and party solidarity - the transfer of votes in the udaras-na-gaeltachta election of 1979 - Parker, Aj (Economic & Social Studies, 1984)
Two important features of the Irish electoral system are localism and party solidarity. The electorate, particularly in rural areas, expect their representatives to look after their specific local interests and are therefore attracted more to voting for a person from "their" area. Whilst there is a basic level of bedrock support for the major political parties in the country, parties recognise the danger of not providing most electors with a candidate with whom they can identify. Without such a candidate, irrespective of his chances of winning a seat, there is always the likelihood that party supporters in an area may turn to a rival party's local candidate. The need for a geographical spread of candidates in constituencies is reinforced by the fact that, in general, party solidarity in terms of transfers is high. Once a vote is captured for a particular party it is more likely to subsequently transfer to party colleagues from other parts of the constituency than to leak to other parties' candidates or become non-transferable, the latter being wasted votes from a party viewpoint.
Keywords: Economics; Sociology